Gender Representation on Reading Texts, Dialogues and Pictures in â€œWhen English Rings a Bellâ€ for Grade VII Junior High School - Hafidhoh, Nur Laila; Faridi, Abdurrahman; Saleh, Mursid (English Education Journal, 2018)
This study focuses on gender representation of reading texts, dialogues and pictures in a textbook â€œWhen English Rings a Bellâ€ for Grade VII Junior High School. It used a descriptive qualitative approach, and its objective was both to investigate gender representation in the reading texts, dialogues and pictures, and to describe the differences and similarities of each representation. The study revealed that female domination was found in the reading texts as seen from gender visibility, gender specific noun, and male domination was seen from gender stereotype. Similarly, female domination was also found in the dialogues as seen from gender visibility and gender specific noun, while male domination was seen from gender stereotype. However, male domination was found in the pictures as seen from gender visibility and gender stereotype. Hence, both the reading texts and the dialogues showed female domination as seen from gender visibility, gender neutral, and gender specific noun. They also presented gender stereotype showing male domination. On the other hand, the pictures showed male domination. In conclusion, the textbook was dominated by female representation in term of the reading texts and the dialogues, and by male representation in term of the pictures. It also contained gender stereotypes placing females less dominant than males.